The girl with the lower back tattoo [compact disc, unabridged] - Schumer, Amy (Simon & Schuster Audio, 2016)
Never one to shy away from the uproarious, challenging, and remarkable moments that make up life, this exceptionally candid book will have readers wincing with recognition, nodding their head in solidarity, and laughing out loud. Written with Amy's signature candor, she reflects on her often raucous childhood antics, her hard won and incomparable rise to comedic stardom, and the courage it takes to approach the world with astounding honesty every single day.